Peran Public Relations sebagai Mediator dalam Program Advokasi : Studi Kasus Sosialisasi Buku Teks Hukum Persaingan Usaha KPPU - Alia Saputri; Witanti Prihatiningsih; Yudie Aprianto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study examines the role of Public Relations (PR) as a mediator in an advocacy program through disseminating the Competition Law Textbook conducted by the Indonesian Competition Commission (KPPU). A qualitative approach using a descriptive case study method was employed through observation, in-depth interviews, and documentation. Data were analyzed using the four stages of PR management developed by Cutlip, Center, and Broom, combined with the Power-Interest Matrix. The findings indicate that KPPU implemented fact finding, planning and programming, action and communication, and evaluation systematically. At each stage, PR mediated organizational interests and stakeholder needs by translating complex competition law concepts into accessible and relevant information. Stakeholder analysis identified the Ministry of Higher Education, university leaders, lecturers, and students as key players because they possess high levels of power and interest. PR also adapted communication approaches according to stakeholder characteristics to strengthen message acceptance and engagement. The study concludes that advocacy effectiveness depends not only on the quality of advocacy materials but also on PR’s capacity to identify strategic stakeholders, manage communication, and adapt strategies to their needs and characteristics effectively.